‘Iddah Wanita Hamil yang Melakukan Aborsi: (Studi Komparasi Antara Mazhab Syafi’i dan Mazhab Maliki) - Ubaidillah, M. Burhanuddin; Wahid Azza, Abdul (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Abortion in general is the termination of pregnancy before the 16th week, where placentation has not been completed. Specifically, abortion is an act of separating the fetus from the mother before delivery is completed according to custom, whether it is done by the pregnant woman herself or by someone else, through methods such as striking the pregnant woman’s abdomen, shocking her, administering medicine, or other methods. Iddah is the waiting period for a woman, based on her menstrual or purity cycle, or after childbirth. The obligation of iddah applies only to women, with the purpose of determining the cleanliness of the womb, for worship (ta'abbud), or for mourning (tafajju') following the death of her husband. During this period, a woman (wife) is prohibited from marrying another man. Broadly speaking, both the Shafi’i and Maliki schools agree on the concept of iddah, referring to the verse in QS. al-Talaq, verse 4. However, the Shafi’i and Maliki schools differ in interpreting the meaning of al-Haml. In the context of the iddah of a woman pregnant due to abortion, the Shafi’i and Maliki schools also differ in opinion. This results in differing views regarding the legality of abortion. Therefore, this article focuses on a Comparative Study of the Iddah of Women Who Have Had an Abortion from the Perspective of the Maliki and Shafi’i Schools. The discussion begins with a General Overview of Iddah and Abortion, the Iddah of a Woman Pregnant Due to Abortion from the Perspective of the Shafi’i and Hanafi Schools, to identify the similarities and differences in opinion from the Perspectives of the Shafi’i and Maliki Schools.